Retrospective drug utilization review of meropenem and role of infectious disease pharmacist in specialized cancer care hospital. (June 2022) - Khan, Muhammad Rehan; Saleem, Zikria; Batool, Narjis; Babar, Mahrukh; Shabbir, Aleena
Objectives: Carbapenem antimicrobials are considered for the treatment of serious bacterial infections. The objective of this study was to review the use of meropenem in cancer patients and to evaluate the impact of clinical pharmacist's intervention in this practice to reduce possible risks associated with use of meropenem. Methods: This retrospective study was conducted among 100 patients who received meropenem at hospital. A structured questionnaire was used to collect data. Descriptive statistics was used to analyze the collected data. Results: A total of 100 patients were included in this retrospective study with aim to review rationality and possible side effects associated with meropenem use in our study population. It was revealed that meropenem used was associated with rise in bilirubin in many of our study patients. Pharmacist were found to be instrumental in placing timely interventions for either de-escalation or switch of meropenem to imipenem/cilastatin to reduce that risk. Interventions were accepted by physicians in most of the cases. Conclusion: De-escalation and switching were performed in accordance with pharmacist recommendations in more than half of study population with empirically started/ study population in which meropenem was used.